(untitled) (AYUSHDHARA, 2021)
Ayurveda is a science of life or art of longevity which encompasses far more than mere therapeutic art. The paragon of beauty of Ayurveda is that it always emphasizes preventive over cure. Kanchnar mentioned as Gandmalanashak varga by Priyavrat Sharma in his book Dravyagun Vigyana part-2. Bauhinia variegata Linn (Family- Caesalpiniaceae) is the botanical name of Kanchnar or syn. Gandaari. Kanchnar is the Galgandnashka by Guna Prabhava. Nowadays, the use of herbal drugs for treatment of various diseases is developing all over the world. In Ayurveda Galganda and Gandmala are co-related with the disorder caused by Thyroid gland dysfunction. The diseases like Galganda and Gandamala are now days become more prevailing condition because of sedentary lifestyle, diet, stress and because of hormonal imbalance. In contemporary system of medicine advices Thyroxin and carbimazole for long standing, may lead to complication and adverse effect on the body. Hence it is necessary to explore safe treatment modalities. Kanchnar used as Ekala dravya in the treatment of thyroid gland dysfunction on the basis of its immunomodulator activity, anti-tumor and anti- cancer activity. Kanchnar is considered as drug of choice for all kind of Granthies. Ayurvedic medicine has the potential to make an important therapeutic contribution. This review article contain spectrum of information about Bauhinia variegata.